2000
DOI: 10.1006/anbo.2000.1153
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Microgravity on Ultrastructure and Storage Reserves in Seeds of Brassica rapa L.

Abstract: Successful plant reproduction under spaceflight conditions has been problematic in the past. During a 122 d opportunity on the Mir space station, full life cycles of Brassica rapa L. were completed in microgravity in a series of three experiments in the Svet greenhouse. Ultrastructural and cytochemical analyses of storage reserves in mature dry seeds produced in these experiments were compared with those of seeds produced during a high-fidelity ground control. Additional analyses were performed on developing B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 22 publications
1
45
0
Order By: Relevance
“…The high forced airflow rates (2-3 m/s) and accompanying ethylene removal provided by ADVASC improved growing conditions for the aerial part of the plants when compared to the previous studies by Kuang et al (2000) and Merkys and Laurinavicius (1983).…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…The high forced airflow rates (2-3 m/s) and accompanying ethylene removal provided by ADVASC improved growing conditions for the aerial part of the plants when compared to the previous studies by Kuang et al (2000) and Merkys and Laurinavicius (1983).…”
Section: Discussionmentioning
confidence: 77%
“…Other symptoms may include aberrant deposition of starch grains and thickened cell walls (Ramonell et al, 2001). In a full life-cycle experiment with Brassica, Kuang et al (2000) found protein bodies that were 44% smaller (cross-sectional area). There was an accompanying 80% reduction in the cotyledon cell number, and starch grains were aberrantly deposited in the seed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations